Smart Health Monitoring System Based On Internet Of Things - Senthur N. S, Senthur N. S; Vanathi A, Vanathi A; T. Livingston, T. Livingston; Gavya, Gavya; Rao, K Srinivas (Journal of Neonatal Surgery, 2025)
The design and construction of an Internet of Things (IoT)-based health monitoring system is presented in this study. This study looks at a comprehensive health monitoring system that is used to track a patient's several health indicators in real time. The research consists of several health monitoring sensors that helps the Doctors and Paramedical staff to monitor the patient efficiently and reduce the time of the health in charges. The Design consists of Pulse oximeter sensors, Body temperature monitoring sensor and Respiratory monitor sensor to monitor the health efficiently. The signal from the pulse oximeter sensor, Body temperature monitoring sensor and Respiratory monitor sensor are collected and the data are transferred to the mobile device via the ESP 32 WIFI module with the help of Arduino UNO. The collected data can also monitor through LCD display and the graphical representation of the reading are displayed via Thing Speak IoT software. The topic of this study is effective patient and senior citizen monitoring. This technology allows for the monitoring of the patient's temperature, blood oxygen level (SpO2), pulse rate, and breathing pattern. This study introduces an Internet of Things-based solution that will make it easier and less expensive to use a medical gadget that would otherwise be difficult to use while at home. Every measurement used to ascertain the patient's health parameters has a 95% confidence interval with a maximum relative error of 5%. The general public's employment of these technologies as support aids in a particular circumstance may significantly affect their own life.